Sponge Density and Distribution Constrained by Fluid Forcing in the Deep Sea - Culwick, Timothy; Phillips, Jeremy; Goodwin, Claire; Rayfield, Emily J.; Hendry, Katharine R. (Frontiers in Marine Science, 2020)
Understanding the distribution and density of sponge grounds in the deep sea is key to appreciating the ecological importance, vulnerability, and role in ocean biogeochemistry of these important habitats. A novel combination of clustering analysis and fluid flow finite element modelling was used to study distribution of four sponge grounds from the Labrador Sea, which were chosen for their distinct assemblages of sponges. Significant small-scale clustering patterns of sponges were found within each sponge ground, measured using the Ripley K function. A new approach using finite element modelling of fluid flow was then applied to understand the drivers of the observed sponge distribution, with detailed numerical experiments providing insights into the flow patterns that could not be obtained from field measurements. Simulations using idealised sponge shapes suggested that sponge wakes could interact and influence the mean flow conditions at the spacings observed within the sponge grounds. Simulations of flow over topographic models of the sponge grounds showed that these interacting wakes generated a boundary layer of slowed flow, which may be beneficial to sponge development. The boundary layer may be acting as a protective layer, affecting larval recruitment, increasing particle fall out and increasing the effective radius of pumping. This observation has important implications for the impact of anthropogenic damage on sponge grounds, which changes the sponge distribution and may reduce the boundary layer thickness, affecting potential recovery rates. This study illustrates the power of incorporating mathematical modelling with field observations in the deep sea to increase our understanding of anthropogenic and climate change impacts on sponge ground ecosystem structure and function.